THE CORRELATION BETWEEN VOCABULARY MASTERY AND SPEAKING SKILL OF THE SEVENTH GRADE STUDENTS OF SMPN 1 KERAMBITAN IN ACADEMIC YEAR 2020/2021 - Desak Putu Novia Puspita Sari; Luh Ketut Sri Widhiasih; Nengah Dwi Handayani (Academic Journal on English Studies (AJOES), 2021)
The aims of this present study were to find the correlation between vocabulary mastery andspeaking skill of the seventh grade students of SMPN 1 Kerambitan in academic year2020/2021. The samples were selected by applying cluster sampling methods by lottery systemso that there were two classes with total students is 66. In order to obtain the data, researchersused two tests; cloze task for measuring vocabulary mastery and picture description formeasuring speaking skill. Furthermore, data collected were analysed by mean of Normalitytest, Homogeneity test, Pearson product moment and T-testing. The data were analysed byusing SPSS version 23. The data analysis showed that there was a significant correlationbetween vocabulary mastery and speaking skill of the seventh grade students of SMPN 1Kerambitan in academic year 2020/2021.